2017
DOI: 10.1111/apa.13872
|View full text |Cite
|
Sign up to set email alerts
|

Receiving early information and trusting Swedish child health centre nurses increased parents’ willingness to vaccinate against rotavirus infections

Abstract: Early information, extra information for parents with less education and close positive relationships between parents and child health nurses were important factors in high rotavirus vaccination rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 31 publications
(61 reference statements)
2
23
0
1
Order By: Relevance
“…During the study period, the vaccination coverage was increased from 76.1 to 81.0% and the hospital admissions due to acute gastroenteritis decreased up to 60% among the youngest in J€ onk€ oping County. In this study, results regarding knowledge and beliefs are in line with previous studies from Stockholm, Sweden (19) and other countries (16,18). According to the national programme for Child Health Services in Sweden, the Child Health nurses meet with the parents within the first couple of weeks after delivery and thereafter on regular, structured health visits.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…During the study period, the vaccination coverage was increased from 76.1 to 81.0% and the hospital admissions due to acute gastroenteritis decreased up to 60% among the youngest in J€ onk€ oping County. In this study, results regarding knowledge and beliefs are in line with previous studies from Stockholm, Sweden (19) and other countries (16,18). According to the national programme for Child Health Services in Sweden, the Child Health nurses meet with the parents within the first couple of weeks after delivery and thereafter on regular, structured health visits.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, results regarding knowledge and beliefs are in line with previous studies from Stockholm, Sweden and other countries . According to the national programme for Child Health Services in Sweden, the Child Health nurses meet with the parents within the first couple of weeks after delivery and thereafter on regular, structured health visits.…”
Section: Discussionsupporting
confidence: 86%
“…A cross-sectional study conducted in Sweden showed that parents did not consider RVGE as a serious illness. 36 While there was a prevailing high level of awareness among participants that dehydration led to hospitalization, our study highlighted a high level of unawareness towards dehydration being an important symptom for RVGE disease (mean: 57% aware). The link between RV gastroenteritis and dehydration was the highest (75%) in Poland; although no government reimbursed universal RV vaccination has been adopted in this country.…”
Section: Discussionmentioning
confidence: 52%
“…Assim, a falta de uma sala de vacinação, bem como de imunobiológicos, pode ser uma barreira à imunização e também influenciar no quotidiano do trabalho em vacinação, pois a ausência de vacinas compromete a busca ativa e contribui para o atraso vacinal. (24,25). Desse modo, o lugar faz ligação, tornando-se laço "onde circulam informações, rumores, imagens, palavras em geral, afetos" (26).…”
Section: Discussionunclassified